Optimisation of fermentation condition for production of hight monacolin k (mk) yield by monascus-strains (Bangladesh Journal of Botany, 2024)
Monacolin K (MK), produced by Monascus fermentation, has significant hypolipidemic effects. In this study, under solid-state fermentation (SSF) quinoa was used as substrate to investigate the effect of the MK production by Monascus species quinoa. The results of the single factor experiment showed that the amount of the substrate loaded, addition of water to the substrate, and fermentation temperature change time have a significant effect on the MK production of Monascus-fermented quinoa. It was found that neither M. pilosus-fermented quinoa nor M. ruber-fermented quinoa produced citrinin. Consequently, these three factors were selected for the response surface optimization to determine the optimal fermentation process. The results showed that the optimal fermentation process of M. pilosus-fermented quinoa was as follows: quinoa loading amount of 30 g/300 ml, addition of 20 ml water to substrate, seed liquid inoculation volume of 10%, cultured at 30°C for 2 days, followed by a temperature change to 25°C and continued cultivation until 12 days. Under this fermentation process, the yield of MK reached 2.51 mg/g and without production of any citrinin. The optimal fermentation process of M. ruber-fermented quinoa was as follows: quinoa loading amount of 31 g/300 ml, water addition of substrate of 20 ml, seed liquid inoculation volume of 20%, cultured at 30°C for 2 days, followed by a temperature change to 25°C and continued cultivation until 12 days. Under this fermentation process, the yield of MK reached 3.22 mg/g and without any citrinin production.Bangladesh J. Bot. 53(3): 717-729, 2024 (September) Special